Bottom–Up Assessment Framework for Electrification Options in Energy-Intensive Process Industries - Holger Wiertzema; Elin Svensson; Simon Harvey (Frontiers in Energy Research, 2020)
Electrification of industrial processes is one of the frequently discussed options to reduce greenhouse gas emissions from energy-intensive industries. This paper presents a bottom–up framework to assess process electrification options for energy-intensive industrial process plants in terms of greenhouse gas emissions and energy costs. The framework is based upon pinch analysis energy targetting methods, and accounts for site-specific conditions, including the effects on heat recovery potential and overall mass and energy balances. Furthermore, interactions between the process site and the background energy system are considered and scenarios are introduced in order to assess the impact of electrification options under different possible future energy market conditions. The framework is illustrated by a case study for an existing chemical plant for which there is a broad variety of electrification options that affect the process in different ways. The option of replacing the natural gas based syngas production unit with electrified syngas and steam production is analysed in detail. The results indicate natural gas savings of 173 MW whereas the electricity demand increases by 267 MW, leading to a strong increase in energy costs but also avoided greenhouse gas emissions of 333 kt/a. For two selected energy market scenarios for 2030 and 2040, the energy costs increase by 59 and 50 M€/a, respectively. The framework can be used to compare electrification with other process greenhouse gas emission reduction measures and to support policy and industrial decision making.